The potential impact of AIDS on population and economic growth rates - Brown, Lynn R. (International Food Policy Research Institute, 1996)
This paper examines the current status of HIV/AIDS infection, particularly in Sub-Saharan Africa, and reviews existing models that look at the future impact that the disease is likely to have on population growth, economic growth, and food security, especially as it spreads to rural areas. Because population growth is considered by many to be the foremost problem facing developing countries in 2020, the paper addresses the question of whether population growth kept in check by AIDS mortality might lead to greater availability of food in 2020 than would be possible without AIDS.